2017
DOI: 10.3389/fphar.2017.00537
|View full text |Cite
|
Sign up to set email alerts
|

Picrorhiza kurroa Enhances β-Cell Mass Proliferation and Insulin Secretion in Streptozotocin Evoked β-Cell Damage in Rats

Abstract: Autoimmune destruction of insulin producing pancreatic β-cells leads to insulin insufficiency and hyperglycemia in type 1 diabetes mellitus. Regeneration of β-cells is one of the proposed treatment for type 1 diabetes and insulin insufficiency. Picrorhiza kurroa is a medicinal herb and is traditionally being used for the treatment of various diseases. Previous studies reported the hypoglycemic potential of P. kurroa. However, its potential role in β-cell induction in insulin secretion have not been fully inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 53 publications
0
25
0
2
Order By: Relevance
“…Aqueous ethanol extract of P. kurroa rhizomes demonstrated antibiabetic activity. Treatment with P. kurroa rhizomes extract (100 and 200 mg/kg) for 30 d significantly decreased high blood glucose and restored the normal levels of serum biochemistry [90] .…”
Section: Biological Activitiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Aqueous ethanol extract of P. kurroa rhizomes demonstrated antibiabetic activity. Treatment with P. kurroa rhizomes extract (100 and 200 mg/kg) for 30 d significantly decreased high blood glucose and restored the normal levels of serum biochemistry [90] .…”
Section: Biological Activitiesmentioning
confidence: 90%
“…16. 6-Hydroxy-1a-(hydroxymethyl)-1a,1b,2,5a,6,6a-hexahydrooxireno [4,5] cyclopenta [1,2- , reported from the different parts of a plant like rhizomes, leaves and stems using different solvents like methanol, ethanol, n-butanol, chloroform, water, and methanol:water (1:1) [75,[83][84][85][86][87][88][89][90][91][92][93] while in P. scrophulariiflora there are 12 glycosides (27-35),…”
Section: -Methoxy-mentioning
confidence: 99%
“…Then first-strand complementary DNA (cDNA) was generated by a random hexamer primer with a cDNA synthesis kit (Thermo Scientific, Hudson, NH, USA). The primer pairs were synthesized according to the method described previously [ 4 , 10 ]. The primers were purchased from Bioneer (Daejeon, Republic of Korea) and β-actin was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin-secreting β-cells failure is a common feature of diabetes, which leads to relative or absolute insulin deficiency. The inflammatory mediators have been concerned as having a crucial role in the prolonged suppression of β-cells apoptosis, β-cells function, and progressive β-cells loss [ 4 ]. Evidence is growing that interleukin (IL)-1β, tumor necrosis factor α (TNF-α), and interferon γ (IFN-γ) are candidate cytokines that participate in promoting β-cells death with some combined effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, medicinal plants with hypoglycemic activities and low adverse effects are gaining importance. Ethno-medical studies revealed that extracts and isolated molecules derived from medicinal plants can be used to treat T1DM [5].…”
Section: Introductionmentioning
confidence: 99%